Study of Ba2Li2Si2O7:Eu2+ phosphor for enhancing the luminous flux of white LEDs - Ha Thanh Tung; Huu Phuc Dang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
The best spectrum characteristics and photometric productivities of white light emitting diode (WLED) device possessing light emitting diodes (LEDs) in red rather than phosphor pc/R-WLEDs with the hue fidelity index (Rf) > 97 for correlated color temperatures (CCTs) between 2700 K and 6500 K were attained using the illumination effectiveness (LE) model. We demonstrate four practical pc/R-WLEDs that have indices of Rf and LE of 96–97 and 120–124 lm/W, respectively, under CCT values measured at 2969 K, 4468 K, 5682 K, as well as 6558 K. These LED packages use blue and red LEDs, also phosphors in green as well as yellow, with respective wavelengths of 448 nm, 650 nm, 507 nm, and 586 nm. In the comparison between phosphor-transformed WLED devices (with phosphor conversion) and quantum-dot WLED devices (QD-WLEDs), pc/R-WLEDs make an outstanding performance in competitiveness for high hue generation, particularly under small CCT values, and could eventually replace current pc-WLEDs.